Sensory Evaluation Of Purple Passion Fruit Jelly Candy (Passiflora Edulis f. Edulis Sims) - Rohman, Fikih Fathul; Putu Hemy Ekayani, Ida Ayu; Damiati, Damiati (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to determine the level of consumer acceptance of the innovation of purple passion fruit-based jelly candy products with a formulation of 120ml passion fruit juice, 120g granulated sugar and 35g gelatin. This study uses a quantitative descriptive analysis method, namely only looking for the average value through organoleptic (hedonic) testing. A total of 50 untrained panelists were involved to involved in assessing of color, aroma, taste, and texture attributes using a 5-point Likert scale. The results showed that this product received a positive response with the category "Very Like" in all aspects. The highest average score was obtained in the taste aspect of 4.64, followed by texture 4.54, color 4.52, and aroma 4.32. Based on these results, it is concluded that purple passion fruit jelly candy is very popular with the public and has the potential to be developed as a commercial food product.